2014
DOI: 10.1007/s00223-014-9843-x
|View full text |Cite
|
Sign up to set email alerts
|

Type III Collagen Regulates Osteoblastogenesis and the Quantity of Trabecular Bone

Abstract: Type III Collagen (Col3), a fibril-forming collagen, is a major extracellular matrix component in a variety of internal organs and skin. It is also expressed at high levels during embryonic skeletal development and is expressed by osteoblasts in mature bone. Loss of function mutations in the gene encoding Col3 (Col3a1) are associated with vascular Ehlers Danlos Syndrome (EDS). Although the most significant clinical consequences of this syndrome are associated with catastrophic failure and impaired healing of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 51 publications
3
80
0
3
Order By: Relevance
“…Previously, Col3 haploinsufficient mice were found to express half the amount of Col3 in tissues compared to wild-type littermates 9; 28; 29 . Our recent work confirmed that Col3 expression in long bones of Col3+/− mice is approximately half of that seen in Col3+/+ mice 11 . In this study, using a bilateral closed, transverse tibial fracture mouse model, we show that diminished Col3 leads to decreased bone formation and alterations in remodeling during fracture healing.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Previously, Col3 haploinsufficient mice were found to express half the amount of Col3 in tissues compared to wild-type littermates 9; 28; 29 . Our recent work confirmed that Col3 expression in long bones of Col3+/− mice is approximately half of that seen in Col3+/+ mice 11 . In this study, using a bilateral closed, transverse tibial fracture mouse model, we show that diminished Col3 leads to decreased bone formation and alterations in remodeling during fracture healing.…”
Section: Introductionsupporting
confidence: 84%
“…Specifically, Col3 deficiency results in increased scar deposition by promoting differentiation of myofibroblasts, the key cells that influence pathologic scarring. Furthermore, we have recently shown that Col3 regulates osteoblastogenesis and the quantity of trabecular bone 11 . In addition to its expression in the early fracture callus 4; 12 , several lines of evidence support a role for Col3 in repair and maintenance of bone, including its requirement for growth acceleration of osteoblasts 13 , its potential role in preserving osteogenic potential of mesenchymal stem cells 14 , and its ability to increase angiogenesis 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type III collagen is produced in bone, particularly during healing. Type III collagen mice are embryonic lethal, but analysis of null cells in culture or heterozygous mice suggests that type III collagen promotes differentiation (Volk et al, 2014). The matricellular proteins SPARC (osteonectin) and thrombospondin-2 (Alford et al, 2013) have been implicated in collagen fiber assembly (Alford et al, 2013;Bornstein, 2000;Harris et al, 2011;Rentz et al, 2007;Bradshaw et al, 2003), and also modulate osteoblast lineage progression (Hankenson and Bornstein, 2002;Hankenson et al, 2000;Alford et al, 2009;Delany et al, 2003Delany et al, , 2000.…”
Section: Ecm Network In Terminal Osteoblast Differentiationmentioning
confidence: 99%
“…By contrast, the content of COL-III is far less than that of COL-I. COL-III could be detected in dental pulp and periodontium and it plays a role in the development of trabecular bone through its effects on osteoblast differentiation33. TGF-β1 appeared in tooth morphogenesis and odontoblast differentiation during embryogenesis and could also be detected immunohistochemically in mature human teeth3435.…”
Section: Discussionmentioning
confidence: 98%